ANALYSIS OF АСТ ADHERENCE DURING PATIENT MANAGEMENT IN THE PRIMARY CARE - L.M. Ogorodova; I.V. Shakhova; T.A. Evdokimova; E.V. Deeva; L.A. Korepanova; T.M. Ershova; E.G. Sadovnikova; E.V. Yarovenko; T.G. Dammer; E.V. Archakova; Yu.V. Bronnikova; I.A. Nelikhova; et al. (Union of pediatricians of Russia, 2009)
The article provides the data on the implementation of Childhood Asthma Control Test in the primary care. The authors showed the attitude of children, parents and doctors towards the questionnaire. They demonstrated dynamics of control over the disease assessed in ACT points. They found out that 45% of children, who received the combined therapy, may reveal the total control over asthma. For the very first time, they highlighted information on the arising difficulties during the work with ACT at the ambulatory stage.Key words: bronchial asthma, control, ACT.